Design, manufacturing and applications of composites : proceedings of the Eleventh Joint Canada-Japan Workshop on Composites : First Joint Canada-Japan-Vietnam Workshop on Composites : Ho Chi Minh, Vietnam, August 8-10, 2016 - Hoa, S. V.; Hamada, H.; Duc, Nguyen Dinh (DEStech Publications, Inc., 2017)
This book presents composites research from Canada and Japan. It adds dozens of original papers from Vietnamese materials scientists to reports from Japanese and Canadian researchers. The book covers new materials, such as energy-producing composites, and offers information on advanced manufacturing technologies for fiber-reinforced materials, as well as metal hybrids, active, self-healing and biocomposites. Applications include biomedical implants, piping, automobile parts, fiber-optic sensors, and more
Keywords: Composite materials -- Research -- Congresses.; Composite materials -- Congresses.; elektronické knihy; electronic books